Social Media, the Contradiction of Journalism, and the Dilemmas of News Start-ups in Indonesia - Purnama, Finsensius Yuli; Krisdinanto, Nanang (Komunikator, 2025)
This research focuses on the implications of social media adoption for journalistic practice among news start-ups in Surabaya and Jakarta. Within the framework of news-media logic analysis, technology (including social media) is assumed to amplify the classic contradiction between professional and commercial aspects of journalistic practice. This research explores the extent to which social media amplifies this contradiction and how journalists negotiate it in their daily professional practice. This research uses a qualitative-descriptive approach. The findings show paradoxical results. On the one hand, news start-up journalists try to negotiate the increasingly strong contradictions through the discipline of verification of sources or news material from social media. On the other hand, the monetisation of news content on social media creates new problems in a commercial and professional context, which triggers a stronger dependence on global social media platforms, reduces reader trust, and shifts readers' focus from important and quality news in the media to provocative and sensational commercial news on social media. This research serves as a ‘warning’ to the idealism of digital journalism, in which there is hope that it will be more democratic, transparent, participatory, improve the functioning of democracy, and give more voice to the voiceless